Marriage story - Newman, Randy 1943- (<<The>> Criterion collection, 2020)
"A love story about divorce. A marriage coming apart and a family coming together. Marriage Story is a hilarious and harrowing, sharply observed and deeply compassionate film from the acclaimed writer-director Noah Baumbach. Adam Driver and Scarlett Johansson deliver tour-de-force performances as Charlie, a charismatic New York theater director wedded to his work, and Nicole, an actor, who is ready to change her own life. Their hopes for an amicable divorce fade as they are drawn into a system that pits them against each other and forces them to redefine their relationship and their family." [criterion.com]
Original: Großbritannien, USA 2019
director-approved Blu-Ray special edition features: new 4K digital transfer, supervised by director Noah Baumbach, with 5.1 surround DTS-HD Master Audio soundtrack ; new interview with Baumbach ; "The players", a new program featuring interviews with actors Scarlett Johansson, Adam Driver, Laura Dern, Alan Alda, Julie Hagerty, and Ray Liotta ; "The filmmakers", a new program about the production of the film, featuring interviews with Baumbach, editor Jennifer Lame, production designer Jade Healy, costume designer Mark Bridges, and producer David Heyman ; "The making of 'Marriage story'," a new program featuring behind-the-scenes footage ; new interviews with composer Randy Newman and Baumbach about the film’s score ; new program featuring Baumbach walking viewers through a key location from the film ; trailers ; English subtitles for the deaf and hard of hearing ; plus: notes on the film by novelist Linn Ullmann
Bildformat 1.66:1
Keywords: Film; Blu-Ray-Disc